Redescription of Alburnus kotschyi Steindachner, 1863, with comments on Alburnus sellal adanensis Battalgazi, 1944 (Teleostei: Leuciscidae) - Freyhof, Jörg; Özuluğ, Müfit; Kaya, Cüneyt; Bayçelebi, Esra; Turan, Davut (Zootaxa, 2018)
Alburnus kotschyi is re-described and a neotype is designated. It is found in a small isolated coastal stream at Arsuz at the eastern Mediterranean coast as well as in the Ceyhan and Seyhan River drainages in southern Anatolia. Alburnus adanensis, from the Seyhan River, seems not to have been found again since its first description in 1944 and might be extinct.